Home and Exile in Irene Nemirovsky's Novella Les Mouches d'automne (1931) - Cenedese Marta-Laura (DE GRUYTER POLAND SP Z O O, 2022)
Irene Nemirovsky's novella Les Mouches d'automne (1931. Snow in Autumn, 2007) paints an effective portrait of exile, of the longing for the lost home, and the disorientation that one feels when faced with a reality that is neither recognizable nor understandable. In this article, I analyse Nemirovsky's narrative strategies in relation to spatio-temporal phenomena. My analysis is based on the work of philosophers Mikhail Bakhtin and Gilles Deleuze: Bakhtin's chronotope and Deleuze's crystal-image illuminate how the novella's dominant themes, exile and nostalgia for the home, are irreducible to the cliches of a linear narration and to the simplistic dichotomy home/exile, past/present, and here/there. Instead, Nemirovsky creates a productive tension of overlapping and coalescing space-and time-frames. The philosophical framework provided by Bakhtin and Deleuze is useful to unlock and make visible how this thematic complexity is reflected in the novella's narrative structure. Indeed, my analysis of Les Mouches's chronotopes and crystal images illuminates Nemirovsky's innovative experimentation in the creation of time-space crossings and a/synchronies, and also contributes to extend further our understanding of Nemirovsky's place within the contemporaneous literary panorama.